Investigar en tiempos de crisis: pensar, juzgar, actuar. Research in Times of Crisis: Thoughts, Judgments and Actions - Comesaña Santalices, Gloria M. (Anales del Seminario de Historia de la Filosofía, 2006)
For the purpose of reflecting on the pertinence of philosophy in confronting the challenges of our times, we develop the Arendtian concept of thought as a decisive activity in elucidating the moral character of our actions and in our search for sense which eventually becomes judgment, when we consider the faculties that philosophy inherently contain in relation to human affairs This paper presents intercultural philosophy as an example of how philosophy works in times of crisis